Addition of Fiber To Solution of Fiber Reinforced Composites In Dental - Lukman Aktovianta (Nur Science Institute, 2022)
Along with the times, people's knowledge is increasing, to the awareness to do dental care. Dental care has now become a community need, starting from technical advancements in the installation of stirrups to the installation of dentures. Associated with dental care in the installation of dentures, there are several complaints of dentures that are easily soluble so that they are easily removed.Fiber reinforced compositesis a composite resin with added fiber reinforcement. FRC consists of composite, fiber and silane. Silane in the composite functions ascoupling agent. This is because the composite and fiber cannot bond well, so that between the two requires a coupling agent, namely silane. The use of silane in FRC composites is to improve the bond and help the bond between the composite and the fiber. One of the factors that affect the performance of the silane is the time it takes to dry the silane adhesive. The process of adding fiber will reduce the solubility of the material and water absorption. The results of a review of several studies show that there are differences in the mean values ​​of the two sample groups. The difference in the mean value of the two sample groups was analyzed using a review of previous research journals. The conclusion is that the addition of fiber to FRC with silane affects the solubility of fiber reinforced composites.